Growth of Oil Palm Seedlings in Main Nursery with Application Mo Micronutrients and Mycorrhiza on Podzolic Soil - Putra, Ilham Mado; Deviona, Deviona; Zul, Delita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The development of oil palm plants in nurseries is greatly affected by the type of growing medium used. Podzolic soils have many drawbacks, such as excessive acidity, a high level of exchangeable aluminum, low levels of phosphorus, and a low cation exchange capacity. By incorporating molybdenum and mycorrhizae as micronutrients, it is possible to improve the soil's chemical properties and promote better growth in seedlings. This study aimed to determine the effects of Mo and mycorrhiza applications on the growth of oil palm seedlings in the main nursery using podzolic soil as the planting medium. The research was conducted at an independent oil palm nursery in Sungai Kumango Village, Rokan Hulu Regency, Riau Province, using a factorial Completely Randomized Design with two factors: Mo doses (0, 0,3, and 0,6 g.plant⁻¹) and mycorrhiza doses (0, 5, 50, and 75 g.plant⁻¹), producing 12 treatment combinations with three replications each. Data were analyzed using ANOVA followed by the LSD test at a 5% significance level. The results showed that the application of Mo and mycorrhiza improved the chemical properties of podzolic soil, particularly total N, total K, total P, and CEC. However, neither the interaction nor the individual factors had a significant effect on seedling growth parameters, including plant height increment, number of fronds, and bulb diameter. The highest mycorrhizal infection levels were observed with the combination of Mo 0.6 g.plant⁻¹ and mycorrhiza at 25 g and 75 g.plant⁻¹.